The Effect of Resistance-Endurance Training on the Expression of IGF-1, Akt, and p70s6k Pathway Genes in the Gastrocnemius Muscle of Aged Rats - Maryam Pahlevanzadeh; Ramin Shabani; Alireza Elmiyeh (مجله علوم پزشکی صدرا)
Introduction: Aging is a natural phenomenon accompanied by reduced physical activity and the onset of sarcopenia. Accordingly, this study aimed to investigate the effect of resistance-endurance training on the expression of IGF-1, Akt, and p70s6k pathway genes in the gastrocnemius muscle of aged rats.Methods: In this experimental study, 14 male Wistar rats aged 22 to 24 months were randomly divided into control and resistance-endurance training groups. The training program was conducted for 10 weeks, with three sessions per week. Gene expression levels of IGF-1, Akt, and p70s6k pathway in skeletal muscle were measured using quantitative real-time PCR, and the data were analyzed using an independent t-test.Results: The results showed that, compared to the control group, the resistance-endurance training group exhibited a significant increase in the expression of the IGF-1 gene (P=0.003), Akt (P=0.019), and p70s6k (P=0.004) genes after 10 weeks of training.Conclusion: The findings suggested that resistance-endurance training probably increased the expression of IGF-1, Akt, and p70s6k pathway genes in aged rats. The activation of the Akt /p70s6k signaling pathway was partially induced by autocrine/paracrine response mediated by IGF-1, ultimately leading to muscle hypertrophy. These effects might also apply to humans. Therefore, further research on human samples is recommended.